Cobalt Squadron - Wein, Elizabeth; Noto, Phil (Los Angeles : Disney, Lucasfilm Press, 2017)
Describes the harrowing story of the courageous bomber pilots and technicians of Cobalt Squadron.
At head of title: Star wars, the last Jedi.
Keywords: Star Wars fiction; Science fiction